Influence of Ba[Mg2Al2N4]Eu2+ phosphor particle size on optical properties of the 6000K CPW-LEDs - Phu Tran Tin; Duy-Hung Ha; Tran Thanh Trang; Q. S. Vu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this paper, we consider the red phosphor Ba[Mg2Al2N4]Eu2+ as the novel recommendation for improving the optical properties of the 6000K conformal packaging WLEDs (CPW-LEDs). For this purpose, we investigate the influence of the Ba[Mg2Al2N4]Eu2+ particle size on the optical properties in terms of CCT, CQS, CRI, and LO using the Light Tools and Mat Lab software. From the research results, it can be observed that the optical properties of the 6000K CPW-LEDs are significantly influenced by the size of the Ba[Mg2Al2N4]Eu2+ particle. The CRI and CQS increase from 65 to 67 and 64 to 68 while the size of the Ba[Mg2Al2N4]Eu2+ particle varies from 1 μm to 10 μm, respectively. This research can provide a novel recommendation for LEDs industry at this time.